Application of flue gas desulfurization gypsum improves multiple functions of saline-sodic soils across China. (August 2021) - Wang, Yugang; Wang, Zhufeng; Liang, Feng; Jing, Xin; Feng, Wenting
Abstract: Saline-sodic soils cover ∼10% of the global land surface and deliver various ecosystem services to human society in the arid/semiarid regions. Flue gas desulfurization gypsum (FGDG), a byproduct from coal-fired power plants, is widely used to ameliorate saline-sodic soils. Here, we aimed to quantify the impacts of FGDG application on multiple soil functions across climatic conditions, management practices, and soil types, and to explore how FGDG application affects plant productivity. We conducted a meta-analysis by compiling 2658 pairs of data points with and without FGDG application from 59 locations across China. We found that FGDG application significantly increased crop yield by 91.2% ± 22.5% (mean ± 95% CI) regardless of local climate and soil type, and improved soil quality by reducing soil exchangeable sodium percentage (ESP) by 37.4% ± 9.6% and pH by 8.1% ± 1.7%. Increases in soil productivity were strongly correlated with decreases in soil ESP and pH, suggesting that increases in soil productivity were due to alleviated stress for plant growth. Meanwhile, some heavy elements (e.g., Hg and Ni) increased after FGDG application, likely imposing threats to soil health. Overall, the FGDG application is effective in improving the quality and productivity of saline-sodic soils across China. Our findings suggest that simultaneous assessment of changes in soil water (e.g., water holding capacity and infiltration), nutrient transformation, soil organic matter dynamics, and microbial communities helps disentangle mechanisms that are responsible for optimizing ecosystem service provided by saline-sodic soils after FGDG amendment application. Highlights: FGDG application significantly reduces soil pH and salinity in different magnitudes. FGDG application significantly increases crop yield and plant seedling emergence. Enhanced plant productivity after FGDG application is due to reduced soil salinity. FGDG application may posit negative environmental impacts of saline-sodic soils.